Formation of the Market Tools of the Investment Activities in the Subjects of the Russian Federation - SHVAKOV, Evgeniy Evgenevich; TROTSKOVSKIY, Aleksandr Yakovlevich; GUBERNATOROVA, Elina Viktorovna (Journal of Advanced Research in Law and Economics, 2016)
The article analyzes the formation of the tools of investment activity in the subjects of the Russian Federation. The introduction of market methods into the economic mechanism of the post-socialist Russia has necessitated the formation of the appropriate mechanism to attract investments and perform investment activities. In the subjects of the Russian Federation this process was characterized by a gradual rethinking of approaches towards the creation of investment tools and its dynamic development. On the basis of the analysis of the Russian legislation and law-making activities in the subjects of the Russian Federation the peculiarities of the tools of investment policy creation since 1991 and till the present time are being revealed in the article. Four periods have been identified, which differ significantly from each other both in understanding the goals and tasks of the used instruments to stimulate investment, and the level of complexity of the investment mechanism.
Keywords: forms and methods of attracting investments in post-socialist economies; investment tools of the investment policy in the developing countries; peculiarities of investment tools formation in the Russian regions